Future Acne Therapy MSC Secretome as an Antimicrobial Agent: Literature Review - Putri, Monica Indiasti; Marlina, Marlina; Sudji, Ikhwan Resmala (Jurnal Biologi Tropis, 2025)
Acne vulgaris is a chronic inflammatory skin condition influenced by excess sebum production, bacterial colonization, and host immune responses. Microorganisms, particularly Cutibacterium acnes and Staphylococcus aureus, play a key role in acne pathogenesis and contribute to persistent inflammation. With increasing antibiotic resistance, innovative therapeutic approaches that are effective, safe, and immunomodulatory are urgently required. This literature review aims to evaluate the role of adipose-derived mesenchymal stem cell (ADMSC) secretome in inhibiting acne-causing bacteria. The review was conducted using databases including ResearchGate, PubMed, Google Scholar, and ScienceDirect, using keywords such as secretome, MSC secretome, antibacterial, C. acnes, S. aureus, and acne vulgaris. A total of 13 relevant research articles were identified. The ADMSC secretome contains antimicrobial peptides (e.g., LL-37), cytokines, growth factors, and extracellular vesicles that can disrupt bacterial membranes, enhance phagocytosis, and inhibit biofilm formation. Several studies demonstrate strong inhibitory effects against S. aureus, including resistant strains, while data on C. acnes remains limited but still supports its therapeutic relevance.